Blood glucose monitoring in pediatric patients on cardio-pulmonary bypass - Sonkusale, Manish; Zanwar, Yogesh N.; Kane, Deepa; Patwardhan, Anil M. (International Journal of Contemporary Pediatrics, 2016)
Background: Meticulous blood glucose control during cardio-pulmonary bypass has received a lot of attention recently. Children are more vulnerable to adverse effects of cardio-pulmonary bypass (CPB) on glucose homeostasis. Objectives of the study were to find out changes in blood glucose due to cardio-pulmonary bypass and the Insulin requirements intra - operatively. Methods: A single centre, prospective trial in 130 children undergoing cardiac surgery for congenital cyanotic/ acyanotic heart disease, requiring cardio-pulmonary bypass. We administered dextrose IV 0.5g/kg/hr in pre bypass period to avoid hypoglycemia. Blood glucose levels were measured at various point of time [baseline, after 10 min and then every half hourly during bypass, 30 minutes after bypass and next during the immediate post-operative using a Hemo-cue glucometer]. To control blood glucose on cardio-pulmonary bypass pump, we used inj. Insulin as per study protocol. The statistical analysis was done using paired and unpaired t test & chi square test. Results: We had examined 130 pediatric patients going on CPB for cardiac surgery. Blood glucose was monitored in patients who did not required inj. Insulin (Group II) on bypass for hyperglycemia (n=33) while 97 patients required insulin (Group I) on bypass because of hyperglycemia. 74% of patient required insulin on pump shows that cardio-pulmonary bypass significantly affects glucose homeostasis in children; most of the children (43%) required insulin 30 min after starting cardio-pulmonary bypass. Conclusions: Blood glucose rise in children of congenital cardiac disease was significant after induction of anesthesia; on hypothermic CPB children of congenital cardiac disease may had rising blood glucose trend and the pre-operative blood glucose significantly affects the trend of blood glucose on CPB. The duration of CPB might not significantly affect insulin requirement of pediatric patients. CPB significantly affected glucose homeostasis in children. Hence it seems prudent to administer small amount of IV dextrose in prebypass period to avoid hypoglycemia but rate and dose of insulin should be adjusted as it may affect blood glucose level on CPB.